PERANAN KUALITAS, PELAYANAN DAN HARGA DALAM MENENTUKAN KEPUASAN KONSUMEN TERHADAP RESTORAN FAST FOOD WARALABA DI INDONESIA - Dadi Akhmad Perdana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
Business competition in the culinary industry, especially in fast food franchise restaurants in Indonesia is currently getting tougher, this can be seen by growth of culinary businessman in Indonesia, from small, medium until high scale. Competition in the Fast Food Franchise restaurant industry is influenced by the satisfaction of consumers with the restaurants they have visited, both in terms of product quality, service quality and price of product. These three elements have a very important role in maintaining consumer loyalty and keeping consumers from making repeat purchases and becoming the main actor in Mouth-to-mouth Marketing by telling their relations, or close friends about their satisfaction when visiting the Fast Food restaurant.